2016
DOI: 10.1039/c6ra15384d
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoparticle-decorated two-dimensional titanium carbide with enhanced supercapacitive performance

Abstract: The sandwich-like Ti3C2/ZnO electrode exhibits high-performance for supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…Owing to the increased electrolyte accessible surface area and the additional contribution of pseudocapacitance caused by the MnO 2 , the obtained MnO 2 /Ti 3 C 2 T x composite achieved a specific capacitance of 212 F g −1 , nearly three times higher than that of pristine Ti 3 C 2 T x . Afterward, various transition metal oxides, such as TiO 2 , ZnO, MoO 3 , NiO, and MnO x , were used to form composites with Ti 3 C 2 T x to enhance the electrochemical performance . For example, a ε‐MnO 2 /Ti 3 C 2 T x composite possesses a larger surface area and exhibits a specific capacitance three times greater than that of pristine Ti 3 C 2 T x .…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Owing to the increased electrolyte accessible surface area and the additional contribution of pseudocapacitance caused by the MnO 2 , the obtained MnO 2 /Ti 3 C 2 T x composite achieved a specific capacitance of 212 F g −1 , nearly three times higher than that of pristine Ti 3 C 2 T x . Afterward, various transition metal oxides, such as TiO 2 , ZnO, MoO 3 , NiO, and MnO x , were used to form composites with Ti 3 C 2 T x to enhance the electrochemical performance . For example, a ε‐MnO 2 /Ti 3 C 2 T x composite possesses a larger surface area and exhibits a specific capacitance three times greater than that of pristine Ti 3 C 2 T x .…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Synthesis of Ti 3 C 2 and Ti 3 C 2 /TiO 2 composites.-The synthesis process of Ti 3 AlC 2 was reported in our previous work. 28 Ti 3 C 2 MXene used in this paper was fabricated by etching the as-prepared Ti 3 AlC 2 in 40% HF solution at room temperature (RT, about 25…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported that introduction of transition metal oxides into MXenes is an efficient way to improve the electrochemical properties in supercapacitors [28][29][30][31] and lithium-ion batteries 32,33 . Among the transition metal oxides, titanium dioxide (TiO 2 ) is one of the most widely investigated electrode materials, owing to its low cost, abundant availability and convenient synthesis in nanoscale sizes.…”
mentioning
confidence: 99%
“…The Sn underwent in situ oxidative growth on the MXene surface, and the Hf was also oxidized to coat their composite. [171] Wang et al synthesized an MXene/nickel-aluminum layered double hydroxide (MXene/LDH) with a porous structure based on this method (Figure 7a). In the atomic layer deposition method, a gas of metal elements precursors was mixed with the O 3 oxidizing agent to be deposited on the surface of the MXene film, and the boiling point of metal oxides must be in between the boiling point of the precursors and the treatment temperature.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[285] Therefore, not Ti 3 C 2 T x /LDH Hydrolysis 6 m KOH 1061 F g −1 at 1 A g −1 70% (4 A g −1 , 4000 cycles) [187] PANI/TiO 2 /Ti 3 C 2 T x Hydrothermal and solution mixing 1 m KOH 108.9 F g −1 at 0.5 A g −1 90% (1 A g −1 , 8000 cycles) [186] Ti 3 C 2 T x /PFDs Agitation-assisted polymerization 1 m H 2 SO 4 340 F g −1 at 5 mV s −1 100% (20 mV s −1 , 10 000 cycles) [212] Ti 3 C 2 T x /PPy Agitation-assisted polymerization 1 m H 2 SO 4 416 F g −1 at 5 mV s −1 92% (100 mV s −1 , 25 000 cycles) [73] Ti 3 C 2 T x /PPy Electrochemical polymerization 0.5 m H 2 SO 4 406 F g −1 at 1 mA cm −2 100% (1 mA cm −2 , 20 000 cycles) [202] www.advmatinterfaces.de surprisingly, MXene/metal oxides composites [64,165,166,171,176,184] and MXene/conductive polymers composites have been used as the electrode materials of supercapacitors. [285] Therefore, not Ti 3 C 2 T x /LDH Hydrolysis 6 m KOH 1061 F g −1 at 1 A g −1 70% (4 A g −1 , 4000 cycles) [187] PANI/TiO 2 /Ti 3 C 2 T x Hydrothermal and solution mixing 1 m KOH 108.9 F g −1 at 0.5 A g −1 90% (1 A g −1 , 8000 cycles) [186] Ti 3 C 2 T x /PFDs Agitation-assisted polymerization 1 m H 2 SO 4 340 F g −1 at 5 mV s −1 100% (20 mV s −1 , 10 000 cycles) [212] Ti 3 C 2 T x /PPy Agitation-assisted polymerization 1 m H 2 SO 4 416 F g −1 at 5 mV s −1 92% (100 mV s −1 , 25 000 cycles) [73] Ti 3 C 2 T x /PPy Electrochemical polymerization 0.5 m H 2 SO 4 406 F g −1 at 1 mA cm −2 100% (1 mA cm −2 , 20 000 cycles) [202] www.advmatinterfaces.de surprisingly, MXene/metal oxides composites [64,165,166,171,176,184] and MXene/conductive polymers composites have been used as the electrode materials of supercapacitors.…”
Section: Mxene/metal Oxide-based Supercapacitor Electrodesmentioning
confidence: 99%